Multi-objective Truss Optimization Using Different Types of the BB-BC Algorithm - Milajić Aleksandar; Beljaković Dejan (MATEC Web of Conferences, 2016)
Optimum design of truss structures is considered as a benchmark problem in the field of the structural optimization. In order to solve this hard combinatorial problem, it is necessary to implement adequate optimization tool that would provide sufficiently wide range of possible solutions within a reasonable time as well as to obtain good exploration and exploitation of search space. The aim of presented study was to compare efficiency of different multi-objective algorithms in solving this task.